Tornado over Punjab (MAUSAM, 1978)
A tornado passed over a few villages in the Ludhiana district in Punjab on 10 March 1975. Synoptic situation and meteorological conditions in relation to the stability of the air column the horizontal and vertical distribution of moisture and the wind flow associated with this tornado have been discussed.